Public Interest in Antitrust Enforcement: An Australian Perspective. (June 2020) - Sims, Rod; Woodbridge, Graeme
The Australian Competition and Consumer Commission's (ACCC) objective in enforcing Australia's competition laws is to make markets work in the interests of Australians by protecting and promoting competition. From the ACCC's perspective, it is poor public policy to introduce other objectives, such as reducing income inequality or political influence, into the enforcement of competition laws. If the enforcement of competition laws tries to achieve everything, in the end, it will achieve nothing. Moreover, there are other, more targeted instruments that are much better placed to achieve these other objectives. The ACCC is of the view that business conduct is likely to be anticompetitive if it interferes with the process of competition and harms trading parties on the other side of the market, or is likely to do so. The ACCC places great significance on these two issues to develop, test, and establish theories of harm to competition. While this is the case, the ACCC is of the view that it is not necessary to precisely quantify the degree of harm to establish that conduct is anticompetitive. Imposing such a requirement risks under enforcement of competition laws.